Advances in genetic testing and optimization of clinical management in children and adults with epilepsy. (3rd March 2020) - Scala, Marcello; Bianchi, Amedeo; Bisulli, Francesca; Coppola, Antonietta; Elia, Maurizio; Trivisano, Marina; Pruna, Dario; Pippucci, Tommaso; Canafoglia, Laura; Lattanzi, Simona; Franceschetti, Silvana; Nobile, Carlo; et al.
ABSTRACT: Introduction : Epileptic disorders are a heterogeneous group of medical conditions with epilepsy as the common denominator. Genetic causes, electro-clinical features, and management significantly vary according to the specific condition. Areas covered : Relevant diagnostic advances have been achieved thanks to the advent of Next Generation Sequencing (NGS)-based molecular techniques. These revolutionary tools allow to sequence all coding (whole exome sequencing, WES) and non-coding (whole genome sequencing, WGS) regions of human genome, with a potentially huge impact on patient care and scientific research. Expert opinion : The application of these tests in children and adults with epilepsy has led to the identification of new causative genes, widening the knowledge on the pathophysiology of epilepsy and resulting in therapeutic implications. This review will explore the most recent advancements in genetic testing and provide up-to-date approaches for the choice of the correct test in patients with epilepsy.